HOW SHOCK INDEX HELPS THE ASSESSMENT OF HYPOVOLEMIC SHOCK : A SCOPING REVIEW - Said, Fathia Fakhri Inayati; Kok Mesa, Nofita Dewi; Watunglawar, Crystin Evangelin; Astuti, Dwi Astuti; Makulaina, Fenska Narly (Universitas Aisyah Pringsewu, 2023)
ABSTRACT Shock is a life-threatening condition that can result in death. The need for fast and accurate treatment to identify the severity of shock patients. One of them is by using the Shock Index (SI). If not treated immediately, there will be a risk of death within 24-48 hours. Studies This made For see shock use Index as Predictor of Outcome for Hypovolemic Shock Patients in the Emergency Room. The method used in this study is the Scoping Review in a manner systematic based on PRISM. Determination say key article search use PICO, And say key Which used is shock index OR hypovolemic shock AND emergency department. The process of searching for articles was carried out in several databases, namely ProQuest, EBSCOhost, and PubMed. Research result 12 articles were obtained that met the inclusion criteria and were synthesized. The articles were then reviewed. The shock index (SI) serves as an assessment tool to identify high-risk patients and assist the medical team in providing appropriate management for patients. IS also serves to provide prognostic information to patients and families Keywords: Emergency Department ;Shock Index; Shock Hypovolemic ABSTRAK Syok merupakan kondisi yang mengancam nyawa seseorang yang dapat mengakibatkan kematian. Perlunya penanganan yang cepat dan akurat untuk mengidentifikasi tingkat keparahan pasien-pasien syok. Salah satunya dengan penggunaan Shock Index (SI). Jika tidak diatasi segera maka akan menimbulkan resiko kematian dalam waktu 24-48 jam. Studi ini dibuat untuk melihat penggunaan Shock Index sebagai Predictor Outcome Pasien Shock Hypovolemic di Instalasi Gawat Darurat. Metode yang digunakan pada studi ini adalah Scoping Review yang dilakukan secara sistematik berdasarkan PRISMA. Penentuan kata kunci pencarian artikel menggunakan PICO, dan kata kunci yang digunakan adalah shock index OR shock hypovolemic AND emergency department. Proses pencarian artikel dilakukan pada beberapa database yaitu ProQuest, EBSCOhost, dan PubMed. Hasil Penelitian diperoleh sebanyak 12 artikel yang sesuai dengan kriteria inklusi dan disintesis. Artikel-artikel tersebut kemudian dilakukan review. Shock index (SI) berfungsi sebagai alat penilaian untk mengidentifikasi pasien yang beresiko tinggi dan membantu tim medis dalam memberikan manajemen yang tepat untuk pasien. SI juga berfungsi untuk memberikan informasi prognostic kepada pasien dan keluarga Kata Kunci: Emergency Departement ;Shock Index; Shock Hypovolemic